Students’ Mathematical Critical Thinking Skills And Difficulties in Solving Geometry Problems: An Analysis - Rahmawati; Lalu Wahyu Rizaldi (Jurnal Pendidikan Matematika (JPM), 2025)
Critical thinking is widely recognized as a key competence in mathematics education; however, many students still struggle to apply it when solving problems. This suggests that the role of critical thinking in mathematics learning needs to be examined more closely. This study describes the overall level of students’ mathematical critical thinking skills and investigates the challenges they experience in utilizing these skills during the process of solving geometry problems. A mixed-methods research design was employed involving 76 junior high school students aged 13–14 years. The quantitative phase utilized a paper-and-pencil test to provide an overview of students’ mathematical critical thinking levels, while the qualitative phase explored the specific difficulties students encountered in applying these skills during problem solving. The findings indicate that students’ mathematical critical thinking skills were at a moderate level, with an overall mean score of 65.62. Of the 76 students involved in the study, 13 students (17.1%) were classified in the low category, 50 students (65.8%) were in the medium category, and 13 students (17.1%) were categorized at the high level. The main difficulties identified were related to reasoning coherence, unit representation, and conclusion formulation. The results of this study are expected to provide valuable insights for mathematics teachers in designing more effective instructional strategies to foster students’ critical thinking in geometry learning.